(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the pedagogical and psychological aspects of developing learners’ cognitive activity through innovative types of educational activities. The theoretical foundations of innovative education, types of interactive lessons, and their impact on cognitive processes are examined. The essence of cognitive activity, factors influencing its development, and mechanisms for fostering it through innovative teaching methods are discussed. The role of problem-based learning, project-based activities, interactive technologies, and digital educational tools in enhancing educational effectiveness is substantiated. The findings contribute to fostering independent thinking, creativity, and active learning.